Small-scale food processing in rural development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
New market opportunities are now providing a still largely unexploited niche for smaller-scale food processing. These lie between the hive of activity in the informal sector and the large private or public African businesses, based on...